A Systematic Literature Review of Land Bank Management Strategies, Agrarian Reform, and Land Governance (2020–2025) - M. Nur Kamila Amrullah; Nur Wening (Sekolah Tinggi Pertanahan Nasional, 2026)
Issues of unequal land ownership, protracted agrarian conflicts, and weak legal certainty constitute structural problems that continue to overshadow Indonesia’s national development. In response, the government established the Land Bank through the Job Creation Law and Government Regulation No. 64 of 2021, granting it a strategic mandate to acquire, manage, and distribute land for public interest purposes and agrarian reform. However, its implementation has faced criticism due to its excessive centralization, limited space for public participation, and a tendency to favor investment interests. This study aims to analyze Land Bank management strategies from a land governance perspective using a Systematic Literature Review (SLR) approach. Following the PRISMA framework, data were gathered from six international databases, yielding 22 selected articles published between 2020 and 2025 in esteemed international journals and recognized national journals. The review identifies five main themes: institutional and regulatory frameworks, digitalization of land information systems, land distribution and agrarian reform, international lessons, and implementation challenges in Indonesia. Collectively, these themes represent the foundations, instruments, objectives, references, and practical realities of land policy. The study concludes that the effectiveness of strengthening the Land Bank hinges on its integration with fair, transparent, and participatory land governance principles. Its main contribution is the proposal of an integrated governance model for the land bank as both a conceptual and practical framework for land policy formulation.